Sludge pretreatment before aerobic digestion to enhance pathogen destruction. Issue 2 (1st November 2013) - Sherif, R.; Parker, Wayne J.; Seaman, L.; Seto, P.; Kennedy, K.
Abstract : Bench scale experimentation was completed to assess the potential of using a short residence time pretreatment reactor upstream of aerobic digestion to enhance the destruction of pathogens. The impact of aeration, temperature, hydraulic residence time (HRT), solids concentration, and feeding frequency on the pretreatment process was investigated. Subsequent testing evaluated pathogen destruction resulting from the operation of selected pretreatment conditions in a staged configuration with conventional aerobic digesters. Either highly oxidative or highly reductive conditions were observed to be most effective in reducing the concentrations of E. coli. and Salmonella spp. in the pretreatment reactor. When operated in series with the aerobic digesters, the more highly reducing conditions in pretreatment were found to enhance die-off of the microorganisms in subsequent aerobic digestion compared to the control.